PERSEPSI WISATAWAN TERHADAP PENETAPAN HARGA KULINER PADA EVENT PACU JALUR DI KABUPATEN KUANTAN SINGINGI - Octarien Syamartha; Siti Sofro Sidiq (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research aimed to the tourist perception of culinary pricing at Pacu Jalur event in Kuantan Singingi sub province. This research aims : (1) to knows tourism characteristic who visiting culinary central at Pacu Jalur event in Kuantan Singingi sub province, (2) to knows the tourist perception about culinary pricing of central culinary at Pacu Jalur event in Kuantan Singingi sub province.Sample in this research are using the accidental sampling, so that the writer taken 100 tourist who visiting the central of culinary at Pacu Jalur event in Kuantan Singingi sub province as a sampling in this research.The results of this research indicate that based on the research results obtained on the tourist perception of culinary pricing at Pacu Jalur event in Kuantan Singingi sub province could be good enough. this is proved by the result of the anquetee spreading, observation and interview was doing by researcher.Constraints the tourist perceptions of culinary pricing at Pacu Jalur event ini Kuantan Singingi sub province are: (1) The government of Kuantan Singingi sub province have to more pay attention to the facilities of Pacu Jalur event, have to complete the facilities and keeping the facilities in good condition. (2) The government of Kuantan Singingi sub province have to more pay attention of culinary pricing was increase by the food merchant in so that the seller was not take the self decision to take the culinary pricing. (3) The government of Kuantan Singingi sub province have to more pay attention to improve the cooperation between the food merchant and the tourist.Keyword : Tourist, tourism, culinary pricing, food, facilities.